Veteran and Provider Satisfaction with a Home-Based Telerehabilitation Assessment for Wheelchair Seating and Mobility - Ott, Kaila K.; Schein, Richard M.; Saptono, Andi; Dicianno, Brad E; Schmeler, Mark R. (International Journal of Telerehabilitation, 2020)
The objective of this project was to measure Veteran and provider satisfaction with a home-based telerehabilitation assessment for wheelchair seating and mobility. Forty-three Veterans were seen remotely at their place of residence by a provider, using a VA Video Connect synchronous videoconferencing system. Veteran and provider satisfaction were collected using the Telerehabilitation Questionnaire (TRQ). Mean individual TRQ scores for both Veterans and providers were significantly higher than the scale midpoint of 3.5. Veterans had higher scores than providers for five individual items on the TRQ. Higher scores by Veterans on the technology and quality and clarity of the video and audio likely correspond to the differences in environmental settings in which the visit occurred for the Veteran compared with the provider. High satisfaction scores with the telerehabilitation assessments are likely attributed to the positive working relationship between the provider and the rehabilitation technician, who provided in-person technical support to the Veteran in the home during the wheeled mobility evaluation. Overall, the results indicate a high level of Veteran and provider satisfaction using telerehabilitation for wheelchair seating and mobility evaluations.